STRATEGI KOMUNIKASI MELALUI MEDIA INSTAGRAM DALAM MEMBERIKAN INFORMASI KEPADA MAHASISWA - Ria Listianingrum; Ana Fitriana Poerana; Weni A. Arindawati (Jurnal Pustaka Komunikasi, 2021)
The Instagram account @fisipunsika is an Instagram account used by the admin (communicator) as a medium of communication in providing information to students. The purpose of this study was to find out how the communication strategy carried out by unsika physicists through Instagram media in providing information to students. The research informants were determined by purposive sampling based on certain criteria, using primary and secondary data sources. This research is descriptive qualitative in nature, while the theory used is Lasswell's theory. The results of this study are (1) the communication strategy carried out by unsika physical communicators through Instagram media in providing information to students, namely the admin trying to learn an easy application for sharing information and the techniques performed by the admin as a communicator are not too complicated, only changing the message in verbal into images using the Canva application, (2) the communication strategy of composing messages carried out by the admin of Instagram Fisip UnSika is considered to be able to provide very effective information to students by determining themes and materials with an orientation in order to be able to provide information to students